Geotechnical investigation and slope design feasibility study for the Otjikoto gold mine in Namibia - Pillay, Ohveshlan (My University, 2017)
This research report focuses on the geotechnical analysis and slope design for the construction of the proposed Otjikoto Gold Mine. The report focuses on the characterisation and analysis of the subsurface conditions in the vicinity of the proposed gold mine to the final pit depths. Laboratory testing data together with geotechnical drillhole log data assist with the geotechnical investigation. The analysis of the sub-surface conditions is assessed using the Laubscher (1990) Mining Rock Mass Classification System. Results from the data analysis are used to derive values that are used for limit equilibrium analyses and results derived are then confirmed using numerical methods. Once the optimum slope angles are determined a consequence based rock fall risk analysis is undertaken. As the focus of the study was based on a classic rock mass classification system, strength and experience is added to the knowledge base regarding this system. This allows for a reference point to situations requiring similar solutions.
Thesis is submitted in partial fulfilment for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Geotechnical engineering; Engineering geology; Ground control (Mining)--Namibia